Development and performance evaluation of hierarchical quadrature amplitude modulation (HQAM) for image transmission over wireless channels - Md. Abdul Kader; Farid, Ghani, Prof. Dr.; R. Badlishah, Ahmad, Prof. Madya Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Link to publisher's homepage at http://ieeexplore.ieee.org/